Effect of pistachio seed hull extracts on quality attributes of chicken burger - Al-Juhaimi, Fahad; Adiamo, Oladipupo Q.; Alsawmahi, Omer N.; Gahfoor, Kashif; Sarker, Md. Zaidul Islam; Mohamed Ahmed, Isam A.; Babiker, Elfadil E. (Taylor & Francis, 2017)
The effect of pistachio hull water extracts (PHWE) at different levels on quality of chicken burger during storage at 4 ± 1°C was investigated. Differences between treatments parameters means were separated using analysis of variance (ANOVA). There was no significant difference in fat, protein, and ash contents of the burgers. The increase in PHWE levels increased the cooking yield and moisture retention (MR) in the treated burger from 59.82% to 66.99% and from 44.27% to 54.73%, respec-tively. The treated burgers had significantly (p < 0.05) higher phenolics than untreated. The pH of the burger was decreased with the increase of storage time. As the storage period increased, thiobarbituric acid reactive substance and plate count were increased in untreated burger. The sensory results showed no significant difference in overall acceptability of the burger. The addition of PHWE to chicken burgers improved its quality during storage for up to 10 days at 4 ± 1°C.